Gentrification: Historical Overview and Current Trends - Burova, O. (Социология: теория, методы, маркетинг, 2018)
The article focuses on the phenomenon of gentrification, primarily on its origins, causes and effects. Approaches underscoring the class nature of this phenomenon have been analysed. The author also gives examples of gentrification in cities around the world, including Western Europe and the post-Soviet space.